2021
DOI: 10.3389/fphar.2021.573852
|View full text |Cite
|
Sign up to set email alerts
|

Cost-Effectiveness of Nivolumab Plus Ipilimumab as First-Line Therapy in Advanced Non–small-cell Lung Cancer

Abstract: Purpose: The effectiveness of nivolumab plus ipilimumab for advanced non-small cell lung cancer (NSCLC) has been demonstrated. Decisions have to be made about allocating healthcare resources. Economic evidence could support policy decisions to fund expensive interventions. The current analysis evaluated the cost-effectiveness of nivolumab plus ipilimumab in advanced NSCLC harboring no EGFR or ALK mutations. It is set in the context of the US and China, representing developed and resource-constrained settings, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…In this study (18), the authors indicated that the vial prices of nivolumabipilimumab were discounted by 17%, based on a previously published study (26), and the cost of chemotherapy was $24,437 per patient regardless of histology (27). In the same study (18), the cost of maintenance chemotherapy was $5,887 for nonsquamous NSCLC (27). All remaining sources for drug prices were obtained from the US Medicare and Medicaid Services (25), literature, and publicly available sources (28).…”
Section: Costs and Their Sourcesmentioning
confidence: 79%
See 4 more Smart Citations
“…In this study (18), the authors indicated that the vial prices of nivolumabipilimumab were discounted by 17%, based on a previously published study (26), and the cost of chemotherapy was $24,437 per patient regardless of histology (27). In the same study (18), the cost of maintenance chemotherapy was $5,887 for nonsquamous NSCLC (27). All remaining sources for drug prices were obtained from the US Medicare and Medicaid Services (25), literature, and publicly available sources (28).…”
Section: Costs and Their Sourcesmentioning
confidence: 79%
“…Variable model cycle lengths were adapted, including intervals of one week (18), 3 weeks (21), 6 weeks (19,20,22,23), and one month (17). Similarly, time horizons varied among the CEAs, including 10 years (17,18,20), 20 years (19), and lifetime (21)(22)(23).…”
Section: Model Cycle and Time Horizonmentioning
confidence: 99%
See 3 more Smart Citations